The cultural stereotype of professional groups: Consensus, accessibility and typicality of stereotypic contents - Santos,Ana Sofia (2017)
The purpose of the present work was to measure the stereotypic content of several professional groups in a Portuguese sample, by determining the culturally shared stereotypic attributes, their accessibility and typicality. Study 1 used a spontaneous attribute-generation-task to collect the stereotypic content of 28 professional groups. The frequency of generation was used to measure consensus on the attributes generated. The order of generated attributes was used to determine their accessibility. To further explore the link between attributes and the professional group, a new sample (Study 2) rated how typical each attribute was of the professional group. We map out the usefulness of studying professional stereotypes content.